The The Impact of Implementing Islamic Guidance to Prevent Corruption in Financial Management : English - Kenichi Satria Kaffah; Wahyunengsih Wahyunengsih; Angel Cahya Raudhatul Jannah (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
Financial management is an important unit in the organization system. Financial management is the central for implementing organization activity. In the other hand, financial management in Indonesia often the corruption and manipulating financial data. Transparency International Indonesia (February 2022) rate Indonesia at 96 from 180 country’s in the corruption perception index. So, the budget allocation in a program is not efficient and can have impact on the success of the program. Actually the government of Indonesia have been launching many policy to prevent the corruption. But until now, all policy is fail. This study aimed to analyze how to prevent corruption in financial management with Islamic guidance. This research was used qualitative analyze. the qualitative method aim to describe and analyze character of informant relating to the impact of implementing Islamic guidance to prevent corruption in financial management. According Moleong (2012), research method qualitative is a research method which the results descriptive data in the form of words verbal messages from people whose behavior can observed by researcher. The collecting data method used interview method. Interview is a method of collecting data by asking questions something to someone who is an informant or respondent (Afifuddin, 2009).The interview have 36 questions to know experiences all informant and education received from they parents. We would like to analyze child experience in home, parents education in the golden age, study experience in the school, and work experience. The research result are implementing Islamic guidance since the child, can be prevent corruption when they work in a company. The Islamic guidance importantly pray in 5 times can be develop person to be the honest, obedience, and always on time. All of this nature will be prevent corruption by low moral. In addition, a good work environment and good roles can be impact to prevent corruption opportunity. Just like invironmen will be able to develop behavior the child.